2007
DOI: 10.1128/jvi.00795-07
|View full text |Cite
|
Sign up to set email alerts
|

Bile Acids Promote the Expression of Hepatitis C Virus in Replicon-Harboring Cells

Abstract: Hepatitis C virus (HCV) is a small, enveloped virus with single-stranded and positive-sense RNA and a genome size of ϳ10 kb in the family Flaviviridae (15). Based on genetic variations among HCV isolates, HCV is classified into six genotypes (1 to 6), with several subtypes within each genotype (17). Genotype 1 is the most common in the United States, Europe, and most parts of Asia (17). HCV is a major public health problem as a cause of chronic liver disease, with more than 170 million persistently infected in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 40 publications
2
71
1
Order By: Relevance
“…I also examined these ACAT inhibitors in the replication of hepatitis C virus (HCV) using GS4.1 HCV replicon-bearing cells according to procedures similar to those used for HG23 cells. The replication of HCV was assessed using real-time qRT-PCR as described previously (2).…”
Section: Methodsmentioning
confidence: 99%
“…I also examined these ACAT inhibitors in the replication of hepatitis C virus (HCV) using GS4.1 HCV replicon-bearing cells according to procedures similar to those used for HG23 cells. The replication of HCV was assessed using real-time qRT-PCR as described previously (2).…”
Section: Methodsmentioning
confidence: 99%
“…The FXR/SHP pathway is well developed in hepatic, intestinal, and renal cells and also participates in the regulation of fatty acid (including cholesterol) metabolism and glucose homeostasis (40,41,44). Previously, our group reported that bile acids play an important role in the replication of hepatitis C viruses and porcine enteric caliciviruses (5,6). However, the role of bile acids and other FXR agonists in rotavirus replication has been unknown.…”
mentioning
confidence: 99%
“…This finding has been further validated by another study showing bileacids to target FXRa, resulting in the up-regulation of HBV expression and rendering the host less susceptible to interferon-a treatment (23). Interestingly, bile acidinduced FXR activation has been shown to increase reproduction of other viruses, such as hepatitis C virus (HCV) and Norovirus (52,53).…”
Section: Farnesoid X Receptormentioning
confidence: 76%